Nobody Home: The Effect of Maternal Labor Force Participation on Long-Term Child Outcomes - Venke Furre Haaland; Mari Rege; Mark Votruba (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate how mother's employment during childhood affects long term child outcomes. We utilize rich longitudinal data from Norway covering the entire Norwegian population between the years 1970 to 2007. The data allows us to match all family members and to measure maternal labor force participation throughout the child's entire childhood. Our empirical approach exploits the variation in exposure to a working mother that exists across older and younger siblings in different family types. We compare sibling differences in families where the mother enters the labor force when the children are older and where the mother remains employed full time thereafter, to sibling differences in families where the mother remains out of the labor force during the entirety of her children's adolescent years. Our identification strategy is, therefore, in the spirit of traditional difference-in-differences, the first difference pertaining to the differences in children's ages within a family and the second pertaining to different family types. The analysis suggests that maternal labor force participation has significant and negative effects on years of education and labor market outcomes. However, the effects are small, which supports the notion that maternal labor force participation has, on average, a small effect on long-term outcomes for children.
Keywords: D13; J22; 330; child development; household production; maternal labor force participation